Assessment of Nutrition Knowledge in Pregnant Women of Lahore: An Interview Based Study at Major Hospitals of Lahore During Prenatal Visits - Affaf, Qaswara; Ibne Yousaf, Ahmad; Khadim Hussain, Azzah; Malik, Rameesha; Bint Yousaf, Ayesha; Sikander, Maryam; Bint Yousaf, Maya; Rashid, Laiba (Indus Journal of Bioscience Research, 2024)
Background: The intentions of the following study were to assess women knowledge regarding dietary practices during pregnancy. The study expresses the nutrition related knowledge of pregnant females and its correlation with associated factors of these women. The study also shows the sources of dietary guidance for these women during pregnancy. Method: The study members visited different hospitals of Lahore, interviewed pregnant women and filled questionnaire regarding their knowledge of dietary practices during pregnancy. The statistical tests applied were frequency, percentage, mean, standard deviation, Regression, Kolmogorov-Smirnov test and Spearman’s correlation. Results: 364 questionnaires were finished and analysed using software. Pregnancy related nutrition knowledge was positively correlated with level of education (rs= 0.46, p<0.05) and monthly income (rs=0.27, p<0.05). Only 4.3% of women attained pregnancy scores related to nutrition knowledge above 50%. They mostly get information from their mothers and doctors. Majority of the women recommended increasing intake of supplies from all food groups and fluid. The result indicated that nutritional behaviour of women was characterized by many ill practices. Conclusion: Women interviewed for this research had restricted nutrition knowledge and proper nutrition guidelines were not provided to pregnant women at health care facilities. Women followed insufficient food routines in pregnancies that were mostly directed by mothers of women. The diet of a female during pregnancy has a direct effect on fitness outcomes of mother and child. Many women lacked this information and thus ended with micro-nutrient deficiencies. So there is an alarming need to train women to enhance their knowledge for appropriate dietary patterns to avoid severe outcomes in the form of compromised maternal-child health